Screening of Bipolar Disorders and Characteristics of Symptoms in Various Populations in Surabaya, Indonesia - Margarita M. Maramis; Azimatul Karimah; Erikavitri Yulianti; Yulia F. Bessing (ANIMA Indonesian Psychological Journal, 2017)
Although Bipolar Disorder (BD) is a common mental illness worldwide (1-3%), there was no data about the prevalence of BD or bipolar spectrum disorder in Indonesia. This study aimed to screen bipolar disorders in various communities Surabaya and its variations of symptoms characteristics. Through a cross-sectional design and non-random sampling survey (N = 1,104) was conducted using the Mood Disorder Questionnaire (MDQ), a screening tool for BDs, and validated self-report instrument. The SPSS 17.0 and chi square was used for analysis. Results showed the lifetime proportion of MDQ positive was 10.7% (n = 118). The proportions of MDQ positive by gender were 4.8% males and 5.9% females, no gender (p = .444) and educational background differences (p = .470). The highest proportions of MDQ positive were 4.4% in the 25-60 year group, 4% having an education level of senior high school and 6.7% having unmarried status. Among participants who had MDQ positive, 22% had an awareness of having psychological problems, unfortunately only 5.9% had visited a medical professional. Overall, the lifetime proportion of suspected bipolar disorder spectrum in Surabaya was higher than that reported in other studies. Conducting a periodic research regarding other psychosocial-cultural backgrounds will help clinicians and government identify the exact prevalence of bipolar disorder in the society and their risk factors. Furthermore, it will help to prevent the increased rate of bipolar disorders.